(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present era, consumers are becoming more health conscious due to the increasing health hazards. So consumption of organic food products have increased to a greater extent than ever before. This study aims to research about the key factors influencing consumers’ willingness to pay more for organic food products. The results showed that education and quality attribute of organic food products are the motivating factors to pay a premium price for organic food products.